Profiting from services and solutions : what product-centric firms need to know - Zeithaml, Valarie A.; Salas, Jim.; Bitner, Mary Jo.; Brown, Stephen Walter, 1943- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Designed for executives in companies that manufacture or sell products, this book outlines the challenges of launching a service and solutions business within a product-oriented organization. The target audience-- manufacturers, industrial suppliers, technology firms, and other vendors of business goods--views services and solutions as a means to financial growth, reduced revenue volatility, greater differentiation from the competition, increased share of customer budget, and improved customer satisfaction, loyalty, and lock-in. The authors visualize the transition from products sold to services rendered and identify the challenges that leaders will face during the transformation. To overcome those challenges, the book shows leaders how to manage change in five areas: corporate structure; corporate culture; organizational metrics of performance, growth and investment; individual skills and talent development; and core competencies of collaboration and customization.
Introduction: transitioning from products to services and solutions -- The service infusion continuum -- Company configuration for services and solutions -- Capabilities: skills, training, and technology -- Customization: balancing uniqueness with operational realities -- Collaboration with customers: engaging customers in service and solution design, development, and challenges to offering new services and solutions -- Conclusion: cultivating a service and solution -- Appendix 1. Research approach, resources, and methodology -- Appendix 2. Company interview guide -- About the authors -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 105-114) and index.
Title from PDF title page (viewed on August 21, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Service industries; Manufacturing industries; Production management; New products; solutions; solutions marketing; servitization; service- oriented; service transition; service strategies; service scorecard; service marketing; service leadership; service innovation; service infusion; service design; service continuum; service-centered; product-service systems; organizational culture; integrated solutions; integrated product services; growth through service; customization; customer centricity; collaboration; classification of services; change management; business-to-business; Electronic books